Comparing Moral Judgments of Patients With Frontotemporal Dementia and Frontal Stroke - Báez Buitrago, Sandra Jimena (2014)
Importance Several clinical reports have stated that patients with prefrontal lesions or patients with the behavioral variant of frontotemporal dementia share social cognition impairments. Moral reasoning is impaired in both conditions but there have been few investigations that directly compare this domain in the 2 groups. Observations This work compared the moral judgments of these patient groups using a task designed to disentangle the contributions of intentions and outcomes in moral judgment. For both disorders, patients judged scenarios where the protagonists believed that they would cause harm but did not as being more permissible than the control group. Moreover, patients with frontotemporal dementia judged harmful outcomes in the absence of harmful intentions as less permissible than the control participants. There were no differences between the 2 conditions. Conclusions and Relevance Both disorders involved impairments in integrating intention and outcome information for moral judgment. This study was the first, to our knowledge, to directly compare a social cognition domain in 2 frontal pathologies with different etiology. Our results highlighted the importance of comparing patients with vascular lesions and patients with neurodegenerative diseases